Method of determination of car movement under the fair wind on the sections of yard hump braking positions - Tayirhanov Kh.Z.; Abdullaev B.A.; Djabbarov SH.B.; Mansurov YU. N.; Rahimov R. V. (Global Scientific Publishing, 2022)
Hitherto there have not been investigated zones of yard hump braking positions under the action of fair wind of small magnitude. There have not been analytically defined a car braking path on the sections of hump braking positions. Purpose. The purpose of the investigation is to construct a mathematical model of the car movement on the sections of the hump braking positions, to derive a braking path formula and calculate its values for a specific example
Keywords: calculate; braking; defined; values